Personal Factors Influencing Communication among Teachers and Students of Medical Colleges of Bangladesh: Teachers’ and Students’ Views - Taslima, Kazi; Talukder, Md Humayun Kabir (Bangladesh Journal of Medical Education, 2020)
This descriptive type of cross sectional study was carried out to explore various personal factors that influences communication among medical teachers and students in selected medical colleges of Bangladesh. This study was done over a period of one year from July 2017 to June 2018. Five government & three non-government medical colleges were selected purposively. Students of first, second, third and fourth phases were selected by adopting convenience sampling technique Teachers were selected by convenience sampling technique and for in-depth interview by purposive sampling technique. Medical teachers and students of selected medical colleges were the study population. Total 979 students and 50 teachers were responded through self-administered semi-structured questionnaire with five points Likert scale. Twenty teachers were responded through in-depth interview.Mutual respect (mean=4.44; 4.42), good communication skill (mean=4.40;4.16), listening skill (mean=4.32; 4.12), empathy (mean=4.32;4.32), self-disclosure (mean=4.27,4.42), sharing expectation (mean=4.29;4.28), awareness about own role (mean=4.25,4.34) were highly influencing personal factors that influence communication positively. Use of drugs/tobacco negatively affect communication, This study revealed some important factors that can improve communication .These are friendly relationship among teachers and students, open minded behavior of teachers, student- teachers cooperation, open discussion between teachers and students, morality and religious practice, motivation of students by teachers, understanding each other’s, avoidance of students politics, responsibility of students & teachers etc. This study also revealed communication barriers such as fear and shyness to teachers, humiliation and discrimination of students by teachers and lack of interest of students Addressing these issues at all possible levels, measures should be taken to improve communication among teachers and students in order to improved teaching learning process ; so that ultimate goal of medical education can be achieved. Bangladesh Journal of Medical Education Vol.11(1) 2020: 17-25